Quantitative carcass characteristics and quality of shoulder and loin of crossbred goat kids receiving diets with live yeast (Saccharomyces cerevisiae var. boulardii) - Fernanda Maraquena Soares Pili; Cibele Regina Schneider; Caroline Isabela da Silva; Giovana da Silva Oliveira; Jennifer Braga Altero; Vanessa Duarte; Claudete Regina Alcalde (Semina: Ciências Agrárias, 2021)
The objective of this study was to evaluate the influence of live yeast (Saccharomyces cerevisiae var. boulardii) on the quantitative and qualitative characteristics of the shoulder and loin of Boer x Saanen crossbred goat kids. Twenty-seven carcasses were used, 13 females and 14 uncastrated males with an average age of 192 days, weighing 30.76 kg, distributed in a completely randomised design using a 2 x 2 factorial arrangement (diet and sex). The yeast was added to the feed before pelletising in a proportion of 0.050 g/kg dry matter (DM). When the goats reached an average of 30 kg of live weight, they were slaughtered. No effects of live yeast on quantitative carcass and qualitative characteristics of shoulder and loin were observed. Regarding sex, males had higher slaughter weights (31.73 kg), empty carcass weight (27.98 kg), hot carcass weight (14.39 kg), cold carcass weight (14.22 kg), higher carcass compactness index (0.28 kg/cm), lower slaughter age (176 days) and lower cooling loss (1.20%). For the cut yields, females presented a higher loin yield (11.55%) and males presented a higher neck yield (6.84%). In the shoulder, males presented a higher proportion of bone (18.58%), while females presented a higher proportion of fat (17.09%) and muscle:bone (3.47). In the loin, females showed higher fat deposition (19.54%) in relation to males. The inclusion of yeast Saccharomyces cerevisiae var. boulardii in the crossbred goat kids’ diet did not generate differences in the quantitative and qualitative characteristics of the shoulder and loin.